The Effects of Self Mobilization Technique on Pain and Headache in Patients with Cervicogenic Headache: A Four Week Randomized Clinical Trial - Kaanmalar, Asoghan; Mohd Izham, Mohd Zain; Pradeep, Balakrishnan; Wan Hazmy, Che Hon (INTI International University, 2023)
Introduction: Cervicogenic headache accounts for 15-20% of all chronic and recurrent headaches and it affects 2.2-2.5% of the adult population. It is characterized by unilateral pain originating from the occipital region without side shifts and it is often related to the skeletal and muscular structures of the cervical spine. The zygapophyseal joints of the upper cervical spine are the most frequent contributors for cervicogenic headache. Manual therapy and exercises have been proposed as the initial treatment option addressing the root cause of the problem. This study aims to evaluate the effectiveness of self-mobilization among cervicogenic patients on Numeric Pain Assessment Scale and Headache Disability Index. Methods: Single blinded, randomized clinical trial was done by recruiting 33 subjects. Subjects were clinically diagnosed with chronic headache and mechanical neck pain from KPJUC groups were randomly allocated into two groups using lottery ticket randomization chosen from a concealed container. Subjects were evaluated on a weekly basis for four continuous weeks. Results: Repeated measure ANOVA was used to analyze the effects of the self-SNAG. Significant improvement in pain and HDI scoring were established with p<0.05 within the experimental and control group. However, statistical differences between the control and experimental group were not established but, notable differences in mean and standard deviation were recorded in experimental group compared to control group between baseline and subsequent weeks. Estimated marginal means reveals experimental group shows better improvement compared to the control group over the four weeks. Conclusion: The findings suggest that Mulligans selfSNAG is effective. The intensity of pain reduced in subjects and the HDI scoring indicated improvement.